2019
DOI: 10.1039/c9cp03441b
|View full text |Cite
|
Sign up to set email alerts
|

Elongated magnetic nanoparticles with high-aspect ratio: a nuclear relaxation and specific absorption rate investigation

Abstract: High aspect-ratio elongated nanoparticles with suitable porosity present partially controlled chemico-physical properties to obtain good heating/contrast efficiency for biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…In the case of nanoflowers, the reported SAR values are around 500 W g Fe −1 (H × f = 4.40 × 10 9 A m −1 s −1 ) for a size of 24 nm; 50 and for spindles, the reported SAR values are around 400 W g Fe −1 (H × f = 4.80 × 10 9 A m −1 s −1 ) for the dimensions of 87 × 16 nm. 9 This work opens the possibility of further enhance those values, even in viscous media, through the sample's preassembly forming nano-size chains (in the case of the flowers and the spindles chains, respectively, when oriented parallel or perpendicular with respect to the applied AMF). In addition, this work successfully achieves heating rates exceeding those using non-spherical Fe 3 O 4 /γ-Fe 2 O 3 nanoparticles prepared by aqueous chemistry in highly viscous media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of nanoflowers, the reported SAR values are around 500 W g Fe −1 (H × f = 4.40 × 10 9 A m −1 s −1 ) for a size of 24 nm; 50 and for spindles, the reported SAR values are around 400 W g Fe −1 (H × f = 4.80 × 10 9 A m −1 s −1 ) for the dimensions of 87 × 16 nm. 9 This work opens the possibility of further enhance those values, even in viscous media, through the sample's preassembly forming nano-size chains (in the case of the flowers and the spindles chains, respectively, when oriented parallel or perpendicular with respect to the applied AMF). In addition, this work successfully achieves heating rates exceeding those using non-spherical Fe 3 O 4 /γ-Fe 2 O 3 nanoparticles prepared by aqueous chemistry in highly viscous media.…”
Section: Discussionmentioning
confidence: 99%
“…5 Among MNPs, those presenting anisometric shape have raised great interest in the field of MHT due to their additional shape anisotropy, which has accounted for increased heat performances. In the past years, there has been hectic research on the heat released by anisometric nanoparticles, including nanocubes, 6 nano-octopods, 7 nanoflowers, 8 elongated nanoparticles 9,10 and nanodisks 11 and, in some cases, their corresponding heat release mechanisms. As an example, Cabrera et al reported a large decrease (80% drop) in the SAR of 21 nm magnetite cubes (this size lies in superparamagnetic-ferromagnetic regime) in viscous media (∼100 mPa s), which was attributed to the Brownian relaxation suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elongated magnetic nanoparticles, mainly nanorods, have been of interest in various industrial [61,62], and biomedical applications [63][64][65]. Classification is based on the external energy required for inversion of the magnetization [61].…”
Section: Elongated Nanoparticlesmentioning
confidence: 99%
“…Here, tumor growth was suppressed, and in vivo localization and visualization of the tumor was possible due to the darkening effect promoted by the nanorods in T 2 -weighted MR images. More recently, elongated magnetite nanoparticles were synthesized by an environmentally friendly hydrothermal method, and it was demonstrated that the presence of larger pores resulted in the highest M S value (97 emu g −1 ) and transversal relaxivity (r 2 = 343 s −1 mM −1 ) [63]. It is worth to note that the abovementioned iron oxide nanoparticles have higher transversal relaxivity values than the ones obtained for clinically approved T 2 contrast agents, such as Ferumoxide (Endorem ® or Feridex ® ) and Ferrixan (Resovist ® ) with r 2 values of~98 s −1 mM −1 [181] and~150 s −1 mM −1 [182], respectively.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%